Penerapan Teknologi Kesehatan pada Gaya Hidup dan Tingkat Stres Pasien Gastroesophageal Reflux Disease - Ishomatul Faizah; Muhammad Miftahussurur; Eka Mishbahatul Mar'ah Has (Journal of Telenursing (JOTING), 2023)
This study aims to identify the influence of technology on GERD patients. The research method used is a literature review through electronic databases and websites, namely Scopus—Science Direct, PubMed, ProQuest, and Sage. The research results showed that of the 20 articles, there were articles that reported that lifestyles such as smoking, high BMI, lack of exercise, eating at night, not eating breakfast, and lack of sleep were risk factors for GERD. Apart from that, GERD is a psychosomatic disease, namely a disease that also originates from the mind, where stress, anxiety, and depression are also closely related to the incidence of GERD. Some articles also report that technology can help patients treat and control their diseases. In conclusion, using technology on the lifestyle and stress levels of gastroesophageal reflux disease patients can help patients treat their condition. Keywords: GERD, Technology, Lifestyle, Stress